Rapidly resolving acute subdural hematoma. A case report - Maqsood, Ahmed (Indian Journal of Neurotrauma, 2008)
Rapidly resolving acute subdural hematoma is a rare condition reported infrequently in the literature. A 52 year old man presented with head injury following a road traffic accident. He was drowsy arousable with a GCS score of 13/15. His initial CT brain showed a 0.7mm thick right frontoparietal acute SDH which was managed conservatively. A repeat CT done after an interval of 48 hours showed complete resolution of the Acute SDH with bilateral subdural hypodense collections. He also had associated facial bone and ACF base fractures along with CSF rhinorrhea. Brief review of the literature and possible mechanisms of resolution are discussed.
Keywords: acute subdural hematoma; CSF Rhinorrhea; head injury; rapid resolution